Dissecting of BUMDesa Transparency Based on Governance Principles - Desak Made Mya Yudia Sari; Ida Ayu Nirma Prameswari (Journal of the Community Development in Asia (JCDA), 2022)
This study has the purpose to convey in-depth information on the phenomenon of the concept of transparency regarding minimizing irregularities in the use of funds, preventing public districts, and achieving organizational goals. Observational data, interviews, and documentation were used as the basis for collecting qualitative data. An interpretive descriptive approach is used as a research methodology with the Yin, 2009 case study. Disclosure of the concept of transparency in the accountability of implementation, reporting, and liability of BUMDes Wija Sari shows orderly, budget discipline, participation, accountability, open system, clear and easy to understand standardization, precautionary principles, honesty, promptly, and policy announcements regarding revenue, financial and asset management. The theoretical and practical implications of research can be used as a reference and contribute to management and stakeholders in implementing the concept of transparency. As a highly regulated organization, the key to successful BUMDes transparency has great potential to be replicated by other BUMDes. The limitation of this research is that the researcher only uses informants who are the main key to BUMDes transparency. Keywords: Accountability, BUMDes, Implementation, Liability, Reporting, Transparency.